Two Lives : One Russia - Daniloff, Nicholas (Boston Houghton Mifflin, 1988)
Weaves a double narrative that brings together yesterday's Russia and today's Soviet Union.
Include Illustration and Notes
Keywords: Soviet Union -- Travel -- Russia (Federation)--Moscow -- Politics and government -- Soviet Union. Komitet gosudarstvennoĭ bezopasnosti